PENGARUH KEPEMILIKAN SAHAM MANAJERIAL DAN INSTITUSIONAL PADA STRUKTUR MODAL PERUSAHAAN - DYAH SIH RAHAYU; FAISAL (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2005)
The agency relationship between managers and shareholders has the potential to influence decision-making in the firm which in turn potentially impacts on firm characteristic such as value and capital structure (debt ratio). This paper examines the relationship between ownership structure among managerial and institutional may have a significance relation with capital structure (debt ratio). Data collection is done by using pooling method. 39 firms listed in Jakarta Stock Exchange for period 1999-2001 used as samples. The empirical results provide support previous research that a positive relation between ownership structure with capital structure (debt ratio). The results also suggest that the relation between institutional ownership and capital structure varies across the level oh managerial ownership.